The Use of Songs as an Effective Teaching Strategy for Vocabulary Learning in Basic English Courses - Balanzar, Adriana (CIEX JOURNAL, 2022)
This research was conducted in CIEX (Centro de Idiomas Extranjeros “Ignacio Manuel Altamirano”) language school which is located in Chilpancingo, Guerrero, México. The topic was selected because the researcher has the intention of demonstrating the effectiveness of songs as a strategy to teach vocabulary inside and outside the classroom. This study is important due to the contributions to language teaching and learning. The study gives a clear idea of the results that can be obtained through the use of songs. This research helps teachers notice the effectiveness of songs in acquiring vocabulary. It will also generate critical thinking and new ideas when using them, taking into account students´ and teachers´ suggestions. This study was performed following the principles of qualitative approach. This approach consists of collecting non-numerical data and its techniques are usually determined by surveys, discussion groups and observations. The research is also under the Phenomenological Method which consists of taking into account the world and subjective experience of the students. This approach considers as relevant the opinions of the students and the teachers who lived the experience of the use of songs inside the classroom. To collect data, the researcher designed an interview and an observation guide. The findings were analyzed from the perspective of phenomenology to facilitate interpretation and to allow the main ideas and influenced factors to emerge from the voice of the participants of the study. Two groups of basic English students and two different teachers were chosen as the participants of the study. The sample was four students with different ages, three women and one man. Finally, the application process was carried out by face-to-face classes, just as interviews and observations and as a result, the effectiveness of the most common teaching strategies with songs was identified. The results obtained through the instruments applied at CIEX basic courses are important and become relevant for English Language Teaching. As stated above, it contributes to provide some ideas based on the experience obtained through the application of songs in teaching strategies. It also contributes to understand Gardner’s Theory of Multiple Intelligences, which emphasizes on musical intelligence.